2018
DOI: 10.1111/imcb.12046
|View full text |Cite
|
Sign up to set email alerts
|

Aged neutrophils accumulate in lymphoid tissues from healthy elderly mice and infiltrate T‐ and B‐cell zones

Abstract: The average age of the human population is rising, leading to an increasing burden of age-related diseases, including increased susceptibility to infection. However, immune function can decrease with age which could impact on processes that require a functional immune system. Aging is also characterized by chronic low-grade inflammation which could further impact immune cell function. While changes to neutrophils in blood during aging have been described, little is known in aging lymphoid organs. This study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Accordingly, in aged mice neutrophils have been detected in high numbers in both T‐cell and B‐cell areas of the secondary lymphoid organs (i.e. LNs and spleen) . The increased neutrophil trafficking to lymphoid organs was associated with enhanced life‐span of the infiltrated neutrophils and their altered phenotype.…”
Section: Diversity Of Neutrophil Phenotype and Pathogenic Potential Imentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in aged mice neutrophils have been detected in high numbers in both T‐cell and B‐cell areas of the secondary lymphoid organs (i.e. LNs and spleen) . The increased neutrophil trafficking to lymphoid organs was associated with enhanced life‐span of the infiltrated neutrophils and their altered phenotype.…”
Section: Diversity Of Neutrophil Phenotype and Pathogenic Potential Imentioning
confidence: 99%
“…At present it is unclear what the role of these neutrophils is, but it is speculated that the atypical phenotype of lymphoid organ neutrophils could contribute to ageing‐associated dysregulation of normal adaptive immune responses, e.g. in infections .…”
Section: Diversity Of Neutrophil Phenotype and Pathogenic Potential Imentioning
confidence: 99%
“…For example, human splenic neutrophils were shown to lose their selective perifollicular topography, and to extensively infiltrate the follicular mantle and germinal centre areas of splenic follicles, under systemic inflammatory or infectious disorders . Similarly, in the past few years, several studies performed in immunized or infected mice, or even in healthy elderly mice, have demonstrated that neutrophils can actually accumulate in the B‐cell zones as a consequence of the disruption of the splenic microanatomy and lymph node structure . For instance, a significant neutrophil influx was observed in the B‐cell area of draining lymph nodes after 7 days post‐immunization in a model of adjuvant‐induced emergency granulopoiesis in neutropenic mice .…”
Section: Neutrophils and B Cellsmentioning
confidence: 99%
“…Higher magnification inserts demonstrate the infiltration of G184S neutrophils into the white pulp. Normally, in young mice neutrophils do not enter the white pulp or lymph node follicles (Kamenyeva et al, 2015;Tomay et al, 2018). As mice age, rare neutrophils can be found in the white pulp, and infection or LPS challenge can also cause neutrophils to enter the white pulp or lymph node follicles (Bronte and Pittet, 2013;Kamenyeva et al, 2015).…”
Section: Localization Of Bone Marrow and Peripheral G184s Neutrophilsmentioning
confidence: 99%